Precise video feedback through live annotation of football - Grønvik, Johan (Universitetet i Tromsø, 2012)
The domain of sports analysis is a huge field in sports science. Several different computer systems are available for doing analysis, both expensive and less expensive. Some specialize in specific sports such as football or ice hockey, while others are sports agnostic. However, a common property of most of these systems is that they try to give in-depth and detailed analysis of the sport in question. This thesis proposes and describes a system that provides the user with the ability to annotate interesting happenings during a live sporting event, through a non-invasive mobile device interface. The device permits focus on important happenings by filtering out unnecessary detail. Our system provides corresponding video of the annotations on the same mobile device, thereby facilitating the process of giving video feedback to the involved coaches and players. We have implemented a prototype of the system that enables evaluation of this idea, and through case studies with Tromsø Idrettslag, a Norwegian Premier League football club, we show its usefulness and applicability.